The write rationale : teaching and assessing writing in English home language in the senior phase - Draper, Matthew (School of Education, 2015)
The National Curriculum Statement is the most substantive document framing how English teachers are expected to teach writing in English Home Language in the Senior Phase. However, when its implicit pedagogy is evaluated according to what five decades of research and theory have confirmed as best practice, it is found wanting. This is largely due to its foundation in outcomes-based education, an educational philosophy that asserts that all meaningful learning can and must be expressed in objective, measurable terms. This positivist assumption is intrinsically at odds with how writing should be taught. Writing is both imaginative and social. Writing is imaginative in that it draws on non-rational faculties such as intuition, aesthetic sensibility and discernment as much as - if not more than - rational logical thought; writing resists reduction to measurable components. Writing is social in that to teach writing is to introduce and integrate student writers into a broader community of writers and writing. A content-driven writing pedagogy does not support the high level of interaction required between student and teacher. An alternative writing curriculum is proposed here, one that is based upon the best thinking and practice to emerge out of a long and continuing debate about how to teach writing.